Estudo de fadiga em engrenagens di diferencial de veículos elétricos - Santos, Maria Luiza dos (2025)
This study investigated the fatigue behavior of bevel gears used in electric vehicle differentials, manufactured by the investment casting process from SAE 4320 and DIN 20MnCr5 steels. Four material and heat treatment combinations were evaluated: martempering with tempering and austempering with subzero cooling, both performed after cementation. Characterization involved macro and microstructural analyses by optical and scanning electron microscopy (SEM), microhardness profiles along the cemented layer, and static and sound bending tests on engineering teeth instrumented with strain gauges. The results revealed that martempering conditions presented higher surface hardness, associated with a predominantly martensitic microstructure, in some cases with possible significant fractions of retained austenite, which favored Tooth Flank Initiation Crack (TIFF) failures. On the other hand, the austempering + sub-zero conditions resulted in bainitic microstructures with possible controlled retained austenite, favoring greater energy absorption and a greater number of cycles to fracture. Thus, the austempering + sub-zero treatment, despite presenting lower surface hardness values, demonstrated better fatigue performance and can be recommended for electric vehicle gears subjected to intense cyclic loading.